2009
DOI: 10.1177/1527002508327382
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Performance Over the Duration of Major League Baseball Long-Term Contracts

Abstract: We re-examine incentives in Major League Baseball contracts by considering performance over the duration of the contract. We consider both the incentive to perform in order to maximize the subsequent contract and the disincentive of a fixed salary. We isolate the effect of the latter by controlling for the probability that the contract is the player's last. We find that players who are less likely to sign a subsequent contract have a large and statistically significant reduction in performance compared to expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…This result suggests a dynamic pattern in that early on in the duration of a LTC, the usual guaranteed‐contract disincentive effect dominates the subsequent‐contract incentive effect; but as a player approaches his walk year, the incentive effect dominates the disincentive effect. Similar to the results reported in Krautmann and Solow () regarding the dynamics of hitting performance across the contract period, our results here suggests a parallel dynamic process in regards to a player's availability.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This result suggests a dynamic pattern in that early on in the duration of a LTC, the usual guaranteed‐contract disincentive effect dominates the subsequent‐contract incentive effect; but as a player approaches his walk year, the incentive effect dominates the disincentive effect. Similar to the results reported in Krautmann and Solow () regarding the dynamics of hitting performance across the contract period, our results here suggests a parallel dynamic process in regards to a player's availability.…”
Section: Resultssupporting
confidence: 91%
“…In a previous paper, Krautmann and Solow () found evidence of such strategic behavior across the duration of the contract. Those players who are less likely to sign a subsequent contract have a greater level of shirking throughout the contract period.…”
Section: Motivation and Previous Literaturementioning
confidence: 85%
“…Although some studies report no evidence of opportunistic behavior (Krautmann, 1990;Maxcy, Fort, & Krautmann, 2002), others reveal shirking as a type of opportunistic behavior in sports (Fernie & Metcalf, 1999;Frick, Prinz, & Winkelmann, 2003;Krautmann & Solow, 2009;Lehn, 1982;Scoggings, 1993;Stiroh, 2007). Especially athletes with long-term contracts tend to reduce their efforts strategically.…”
Section: Need Of Incentives In Professional Sportsmentioning
confidence: 99%
“…Such indicators include batting and slugging averages, home runs, or hits in baseball (Ahlstrom, Si, & Kennelly, 1999;Harder, 1991;Krautmann & Solow, 2009;Ou & Wang, 2009;Sommers, 1994); goals, assists, and fouls in football (Frey, Schaffner, Schmidt, & Torgler, 2013;Schmidt, Torgler, & Frey, 2009); and points, rebounds, and steals in basketball (Berri & Krautmann, 2006;Stiroh, 2007). Most elite leagues gather these objective statistical numbers, so data sets are available.…”
Section: Performance Measurement In Team Sportsmentioning
confidence: 99%
“…Parker and Powers (2002) found that members of Congress who are about to leave office spend more on foreign travel knowing that they will not be held accountable by voters. In sports, Krautmann and Solow (2009) found that baseball players who are less likely to sign a subsequent contract performed worse, and Cain (2011) found that hockey players´ performance worsened as the likelihood of retirement increased.…”
Section: Causes Of Inactivity In Late Careermentioning
confidence: 99%